2008
DOI: 10.1002/stc.243
|View full text |Cite
|
Sign up to set email alerts
|

A method for large-scale vulnerability assessment of historic towers

Abstract: The methods commonly pursued for vulnerability or risk analysis, when carried out at large scale (territorial, regional), are mainly based on qualitative parameters, due to the necessity of processing a huge number of structures. As a matter of fact, the final target of these methods is the correlation of the most representative parameters of the structural behaviour, so as to finally rank the same structures according to their level of vulnerability or associated risk.These methods are undoubtedly effective f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 6 publications
0
21
0
1
Order By: Relevance
“…A descrição e a definição detalhada do processo de avaliação da fragilidade sísmica e a consequente avaliação do nível de dano esperado para as várias classes arquitetónicas consideradas é apresentada de forma individual em [2]. Salienta-se, no entanto, que os procedimentos estabelecidos são baseados em [3][4][5][6][7][8], no caso de construções da classe arquitetónica CA1, em [9][10][11][12], no caso de construções da classe arquitetónica CA2, em [13][14][15][16][17][18][19], no caso de construções da classe arquitetónica CA3, e em [20][21][22][23], no caso de construções da classe arquitetónica CA4.…”
Section: Análise Do Nível De Dano Esperadounclassified
“…A descrição e a definição detalhada do processo de avaliação da fragilidade sísmica e a consequente avaliação do nível de dano esperado para as várias classes arquitetónicas consideradas é apresentada de forma individual em [2]. Salienta-se, no entanto, que os procedimentos estabelecidos são baseados em [3][4][5][6][7][8], no caso de construções da classe arquitetónica CA1, em [9][10][11][12], no caso de construções da classe arquitetónica CA2, em [13][14][15][16][17][18][19], no caso de construções da classe arquitetónica CA3, e em [20][21][22][23], no caso de construções da classe arquitetónica CA4.…”
Section: Análise Do Nível De Dano Esperadounclassified
“…The procedure developed for cultural heritage units of class CA2 is similar to that of class CA1. For class CA2, the procedure is based on the classification and weighted average of 12 parameters related to the type of structural system, the characteristics of the masonry, the lateral strength of the structure, the slenderness of the structure, the type of foundations and soil conditions, the construction position and interaction with respect to its surroundings, plan and vertical regularity factors, the type and arrangement of openings, the type of floor and roof systems, the state of conservation of the structural system and the existence of non-structural falling hazards [78][79][80][81]. The procedures developed for cultural heritage units of classes CA3 and CA4 are different than those of classes CA1 and CA2 since they are mostly based on simple mechanics-based approaches.…”
Section: Ca1mentioning
confidence: 99%
“…These structures are characterized by their notable slenderness and also represent one of the main differences from most of the historic structures or even ordinary buildings [1]. These structures are scattered over different countries with different densities and features.…”
Section: Database Collection and Analysismentioning
confidence: 99%
“…Unfortunately, several historical constructions suffered partial or total collapse in the course of time due to earthquakes, fatigue, deterioration, soil movements, etc. The occurrence of these unexpected and unavoidable events has demonstrated that historical slender masonry structures are one of the most vulnerable structural types to suffer strong damage or collapse [1]. These losses are simply not quantifiable in economic terms, as nether lives nor can cultural heritage be reinstated by post-earthquake reconstruction plans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation